The Influence Of Transformational Leadership And Work Environment On The Work Produtivity Of Stockfit Employees At PT Adis Dimension Footwear Tangerang Regency - Alam, Muhamad Nur; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine the simultaneous influence of transformational leadership and the work environment on employee productivity at PT Adis Dimension Footwear, Balaraja, Tangerang.This study employed a quantitative descriptive method, describing variables as they are, supported by numerical data derived from actual conditions. The population in this study was all employees at PT Adis Dimension Footwear, Balaraja, Tangerang. The sample size was 83 respondents. Simple random sampling was used to determine the sample size. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) transformational leadership partially significantly influences employee productivity in the Stockfit department at PT Adis Dimension Footwear, Balaraja, Tangerang, as indicated by the calculated t-value > t-table (6.618 > 1.990), and a significance value of 0.000, which is less than the 0.05 threshold. Therefore, Ha is accepted and H0 is rejected. (2) Partially, the work environment significantly influences the productivity of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t value > t table (2.203 > 1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, transformational leadership and the work environment significantly influence the productivity of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F value > F table (26.219 > 3.11) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of transformational leadership and the work environment, both partially and simultaneously, have a significant influence on the productivity of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang.